Participation in Health Promotion of Monks in Sangha Administrative Area, Region 9 - Sittivongsa, Phra Boonpeng; Kunpalin, Poowanida; Boonmee, Kanokon (Dhammathas Academic Journal, 2019)
The objectives of this research were: 1) to study the conditions of participation; 2) to analyze the influencing factors toward participation; 3) to present the participatory model in health promotion of monks in Sangha administrative area, region 9 as appropriate participatory model. Data were drawn from a set of 390 questionnaires in Sangha The objectives of this research were: 1) to study the conditions of participation; 2) to analyze the influencing factors toward participation; 3) to present the participatory model in health promotion of monks in Sangha administrative area, region 9 as appropriate participatory model. Data were drawn from a set of 390 questionnaires in Sangha administrative area, region 9, with multi-stage random sampling technique, and 44 interview forms or representatives of government and private agencies relating terms of monks’ health promotion. The following statistics were analyzed as follows: frequency, percentage, mean, standard deviation and Stepwise-multiple regression correlation. Research results found that: 1. The conditions of participation of monks in health promotion were at moderate level in 3 aspects, namely setting health promotion policy, implementing health promotion policy, and evaluating health promotion policy. Moreover, all 7 health promotion factors were at the moderate level, such as the participation of the community, the role of the Sangha Supreme Council of Thailand, local roles, the role of the Sangha Supreme Council of Thailand, helping from the network, Government supporting, and leadership of abbots. 2. As crucial factors as to the participation in monks’ health promotion, it revealed that (1) Participation in setting the health promotion policy, consisted of assisting from the networks (X2), the role of the Sangha Supreme Council of Thailand (X7), and community participation (X1), all 3 aspects could predict the participation in setting the health promotion policy at 8.10 percent and at the .05 level of significance; (2) Participation in implementing the health promotion policy, consisted of assisting from networks (X2), community participation (X1), and local roles (X6), these 3 aspects could predict the participation in implementing the health promotion policy at 10.20 percent and at the .05 level of significance; (3) Participation in evaluating the health promotion policy, consisted of community participation (X1), local roles (X6), the role of the Sangha Supreme Council of Thailands (X7), the role of the abbots (X4), and assisting from the networks (X2), these 5 aspects could predict the participation in evaluating the health promotion policy at 90.60 percent and at the .05 level of significance. 3. Participation model in health promotion of monks in Sangha administrative area, region 9, it consisted of participation, review and renovation, development planning, cooperation management and performance evaluation.